Umetna inteligenca in slovenščina - Bavec, Cene (Teorija in praksa, 2026)
The rise of generative artificial intelligence represents far more than the emergence of a new linguistic tool. Namely, it raises fundamental questions about how to preserve smaller languages as fully-fledged vehicles of thought, knowledge, and public discourse. For Slovenian, this transformation signals either a risk leading to its functional recession or an opportunity for its long-term stability. Rather than being limited to a static overview of the current technological market, the article presents analysis of the systemic dynamics of language shifts to establish a strategic framework that remains resilient to rapid changes in operational environments and individual tools. Through the lens of systems theory, the article sheds light on the underlying factors driving the phase transitions that lead to the language being abandoned, while critically evaluating three development scenarios for Slovenia.
Keywords: artificial intelligence; Avtonomija (filozofija); Jezik (jezikoslovje); jezikovna suverenost in vitalnost; linguistic sovereignty and vitality; Slovenian language; slovenščina; strategic scenarios; strateški scenariji; Suverenost; systems theory; teorija sistemov; umetna inteligenca